Análise da vantagem de jogar em casa no voleibol feminino brasileiro - Angioluci Diniz Campos, F.; Pellegrinotti, I. L.; Natale Pasquarelli, B.; Heidi Ozaki, E.; Reeberg Stanganellli, L. C. (Revista Brasileira de Ciência e Movimento, 2015)
The advantage of playing at home, phenomenon known as "home advantage" is the term used by the higher prevalence of victories (over 50%) of the teams playing at home in a balanced table with the same number of games among the teams (at home and away). In women's volleyball, there are few studies that observed this phenomenon and its implications on the skills of the game. The aim of this study was to investigate the advantage of playing at home in women's volleyball and its influence on performance indicators (final actions) on the outcome of the game. The sample consisted of 90 games of women's volleyball leagues (season 2012/2013), totaling 323 sets and 14.356 points. Performance indicators were observed to interfere with the result of the game (win or lose): serve, attack, block and opponent`s error. Data were analyzed using SPSS 17.0 software. Descriptive analysis were performed (mean and standard deviation), and comparisons were made through the Mann-Whitney U test for independent samples when comparing home and away team`s actions points. The level of significance was P<0.05. The results showed that the "home advantage" phenomenon was verified with a higher prevalence of victory for the home teams in the women`s league volleyball (53%).